Determining the yield and chemical characteristics of trimmings from hot processed and traditionally processed cull meat goats - Weber, Lauren Allison (Kansas State University, 2011)
Two experiments were completed as a part of this study. The objective of the first experiment was to determine the differences in chemical characteristics of trimmings from hot processed and traditionally processed cull meat goats. Crossbred cull doe goats (n=18) were assigned to one of 3 kills days with 6 replications per day. The sides of each goat were randomly assigned to hot processed (HP) or traditionally processed (TP). HP sides were fabricated within 2 h of slaughter, ground with 2% salt and dry ice and then held at 2oC for 24h. TP sides were chilled at 2oC for 24 h prior to fabrication and grinding. After sampling, 2% salt was added to remaining trim yielding 2 treatments: traditionally processed with no salt added (TPNS) and traditionally processed with salt added (TPS). As expected, the HP treatment had a higher (P<0.0001) ultimate pH than TP and a higher water holding capacity (WHC) than TPS (P<0.002) and TPNS (P<0.001) treatments. HP and TPNS had significantly higher (P<0.0007 and P<0.0003, respectively) percent moisture than TPS. Percent fat was similar (P>0.19) for all treatments. However, TPNS had more protein (P<0.0001) than either the HP or TPS treatments. HP and TPS had decreasing L* values until d 6 when values increased significantly while TPNS decreased steadily by day. HP and TPS differed significantly from TPNS until d 6 when no significant differences were seen. For all treatments, a* values showed decreasing values until d 6. For all treatments, b* values increased until d 5. The objective of the second experiment was to investigate the viability of composting as a means for disposing of goat tissues resulting from the slaughter and fabrication process. By-products from the slaughter of cull meat goats (n=18) were assigned to 3 treatment piles: bones, offal + head (OH), and whole (bones, skull, and offal). Bones and OH piles increased in temperature, with peaks at wk 7 and wk 9, while whole piles had elevated temperatures from wk 5 to wk 9. Bone piles had statistically lower temperatures through wk 3, but were not statistically different than other treatments through the duration of the study. Whole piles had higher (P<0.0001) temperatures over the 8 wk composting period than OH and bone piles. Bone decomposition progressed over 90 d; at d 60, bones in whole piles had greater (P<0.05) decomposition than in bone piles. Similarly, skulls decomposition increased over the 90 d period. At d 60 and 90, skulls in whole piles had greater (P<0.05) decomposition than skulls in OH piles.
Keywords: compost; decomposition; goat; pH; hot processing; water holding capacity; Agriculture, Animal Pathology (0476); Agriculture, Food Science and Technology (0359); Agriculture, General (0473)